Electronic screen technology use and connection to nature in Canadian adolescents: a mixed methods study - Michaelson, Valerie (Can J Public Health, 2020)
OBJECTIVES: Declines in exposure to nature may deprive young people of experiences that are positive for their mental health. One factor that may interfere with connections to nature is use of electronic screen technologies. The objectives of this study are to (1) document variations in the perceived importance of connections to nature nationally among adolescents; (2) explore relationships between these connections and the use of electronic screens, both epidemiologically and qualitatively; and (3) integrate core findings from both strands in order to provide evidence-based recommendations for health promotion. METHODS: The study involved a mixed methods design. Strand 1 involved a qualitative study of 74 Canadians (ages 10–18, years 2016–2018) with data collected through focus groups and interviews. Strand 2 involved a cross-sectional observational analysis of a national survey of 23,920 Canadians (ages 11–15, years 2013–2014). Findings from both strands were integrated through an established protocol. RESULTS: Increased use of electronic screen technology was consistently associated with lower perceived importance of connections to nature. Barriers to connecting to nature included choices that young people are making, the addictive properties of technology, and beliefs that being indoors is more comfortable and safer than being outdoors. When young people disconnected, their appreciation of being outdoors increased. INTERPRETATION: This novel study showed, quantitatively, that the time young people spend with electronic screens displaces time that they spend engaging in outdoor activities. Deeper reasons why such associations occur emerged in the qualitative strand. Temporary disconnection from screens may lead to renewed opportunities for outdoor exposures.